Kajian Potensi Cadangan Airtanah di Area Kampus Universitas Muhammadiyah Purwokerto Menggunakan Metode Geolistrik - Suwarsito Suwarsito; Radin Alhif Dirgantara; Esti Sarjanti (JRST (Jurnal Riset Sains dan Teknologi), 2021)
The study was purposed to analyze the potential for groundwater reserves in the main campus area of Universitas Muhammadiyah Purwokerto (UMP). The research uses observation method. The data of the study include resistivity, thickness of aquifers and groundwater reserves. Data collection using the geoelectric method application Wenner-Schlumberger configuration consists of 2 lines. Data processing was performed using Microsoft Excel and Res2dinv2D to obtain a 2D resistivity cross section and the type of soil layer with its thickness. Data analysis uses the Darcy equation to obtain the potential amount of groundwater reserves in the form of water discharge (Q). The results showed that the potential for groundwater reserves in the main campus area of UMP was 351.53 m³/day or 4.07 liters/second. According to the Decree of the Minister of Energy and Mineral Resources No.1451 K / 10 / MEM / 2000, the potential for groundwater reserves in the main campus area of UMP was included in the "medium" criteria.